A Drosophila G1-specific cyclin E homolog exhibits different modes of expression during embryogenesis. - Richardson, H.E.; O'Keefe, L.V.; Reed, S.I.; Saint, R. (Development, 1993)
We have isolated a Drosophila homolog of the human G1-specific cyclin E gene. Cyclin E proteins thus constitute an evolutionarily conserved subfamily of metazoan cyclins. The Drosophila cyclin E gene, DmcycE, encodes two proteins with a common C-terminal region and unique N-terminal regions. Unlike other Drosophila cyclins, DmcycE exhibits a dynamic pattern of expression during development. DmcycE is supplied maternally, but at the completion of the cleavage divisions and prior to mitosis 14, the maternal transcripts are rapidly degraded in all cells except the pole (germ) cells. Two modes of DmcycE expression are observed in the subsequent divisions. During cycles 14, 15 and 16 in non-neural cells, DmcycE mRNA levels show no cell-cycle-associated variation. DmcycE expression in these cells is therefore independent of the cell cycle phase. In contrast, expression in proliferating embryonic peripheral nervous system cells occurs during interphase as a brief pulse that initiates before and overlaps with S phase, demonstrating the presence of a G1 phase in these embryonic neural cell cycles. DmcycE appears not to be expressed in cells that undergo endoreplication cycles during polytenization. The structural homology to human cyclin E, the ability of DmcycE to rescue a G1 cyclin-deficient yeast strain, the presence of multiple PEST sequences characteristic of G1-specific cyclins and expression during G1 phase in proliferating peripheral nervous system cells all argue that Drosophila cyclin E is a G1 cyclin. Constitutive DmcycE expression in embryonic cycles lacking a G1 phase, in contrast to expression during the G1-S phase transition in cycles exhibiting a G1 phase, implicates DmcycE expression in the regulation of the G1 to S phase transition during Drosophila embryogenesis.